Pengembangan Sistem Toko Online Hasil Pertanian pada PT. Son menggunakan Framework CodeIgniter - Vira Oktavianis; Edri Yunizal (JATISI, 2026)
Son Shop is a store that sells agricultural products from its own garden and local farmers. However, its transaction management is still manual, leading to issues such as unclear reporting, potential financial losses, and limited consumer reach. To address these challenges, a website-based information system is needed to digitize transaction records and expand marketing through an online store. This study aims to design an efficient, responsive, and user-friendly online store system using the CodeIgniter framework. CodeIgniter was chosen for its speed, flexibility, comprehensive documentation, and ease of maintenance. The research follows the Systems Development Life Cycle (SDLC) methodology, encompassing planning, analysis, design, and implementation stages. The developed system enhances business efficiency, improves reporting clarity, and broadens consumer access. Findings indicate that the system significantly improves transaction management, stock tracking, and financial reporting. By implementing an online store, Son Shop can reach more consumers beyond its local market. Additionally, the digitalization process has substantially reduced transaction recording errors and expedited financial and inventory reporting. Key features of the system include product management, automated transaction recording, real-time sales reports, and easy access for both administrators and consumers.